(untitled) (Third Sector Social Economic Review, 2024)
In a world that is developing rapidly in all areas of life and moving towards becoming a consumer society, it’s very important for individuals to use available resources sparingly. Because if individuals consume resources in a sustainable manner, they can meet their basic needs without damaging existing resources and contribute to the protection of resources for future generations. The family, which is the unit with the most effective role in society in terms of sustainable consumption of resources, consumes resources very intensively in residences. It’s extremely important to examine the sustainable consumption behavior of families, especially considering that they assume a very important role and responsibility in raising future generations. This study, planned to determine the sustainable consumption behaviors of families, was conducted with 995 individuals residing in Çankaya, Keçiören and Sincan districts of Ankara. In the study, the ""Sustainable Consumption Behavior Scale"", developed by Doğan, Bulut and Kökalan Çımrın (2015) and consisting of 17 items, was used to measure individuals’ sustainable consumption behavior. Scheffe and t tests were used to analyze the data. As a result of the study, there was a statistically significant difference between the sustainable consumption behaviors of families and education level, age, income level, gender. The findings were discussed within the framework of studies in the literature and various suggestions were made to families, institutions and organizations.